2002
DOI: 10.1093/pasj/54.4.629
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetrical Distribution of Sunspot Groups in the Solar Hemispheres

Abstract: In the present work, the north–south asymmetry of solar activity was examined by analyzing statistically the hemispheric distribution of annual numbers of sunspot groups, using the Royal Greenwich Observatory data set from the year 1874 through 2000. An interesting phenomenon is found that the solar activity of a cycle usually has the same beginning and end times, but different maximum amplitudes at different maximum times in the hemispheres. Some characteristics of the asymmetry of solar activity were investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The refined consideration reveals, that the expected polarity dominance for cycle 23 is getting more close to the total number of events, but still with a minority of reversed cases in both hemispheres. A hemispheric asymmetry in the distribution of evolving photospheric magnetic flux, as supported by the results of Li et al (2002) who found more sunspot groups appearing in the northern hemisphere of the Sun in the rising to maximum phase of cycle 23, from 1996 until 2000, is not apparent in the PEA frequency distribution.…”
Section: Photospheric Source Regions and Solar Cycle Dependencementioning
confidence: 55%
“…The refined consideration reveals, that the expected polarity dominance for cycle 23 is getting more close to the total number of events, but still with a minority of reversed cases in both hemispheres. A hemispheric asymmetry in the distribution of evolving photospheric magnetic flux, as supported by the results of Li et al (2002) who found more sunspot groups appearing in the northern hemisphere of the Sun in the rising to maximum phase of cycle 23, from 1996 until 2000, is not apparent in the PEA frequency distribution.…”
Section: Photospheric Source Regions and Solar Cycle Dependencementioning
confidence: 55%
“…This is not the whole story, though. Other researchers (Li et al 2002;Norton & Gallagher, 2010) parsed the solar cycle into distinct periods of minimum, rising, maximum, and declining times, then found the phase relationship between the hemispheres during these times. (Of course, the smaller the time period analyzed, the smaller the statistical sample of data becomes, especially during cycle minimum).…”
Section: Hemispheric Phase Lag Based On Sunspot Datamentioning
confidence: 99%
“…Second, the maximum time of solar activity in a normal cycle is usually different in the two hemispheres [ Li et al , 2002a].…”
Section: Fine‐scale Characteristics Of Full‐disk Activity Cyclesmentioning
confidence: 99%